(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
The escalating threat of drug-resistant microorganisms poses a significant challenge to global health, necessitating an urgent and comprehensive review of current strategies and innovations aimed at combating antimicrobial resistance (AMR). AMR not only undermines the effectiveness of existing antibiotics but also complicates treatment protocols, leading to increased morbidity, mortality, and healthcare costs. This review explores the latest advancements and methodologies being developed to address this critical issue, highlighting the multifaceted approaches essential for maintaining the efficacy of antimicrobial therapies. A major focus of current work is to review the discovery and development of novel antibiotics with unique mechanisms of action. Noteworthy examples include teixobactin, which targets Gram-positive bacteria by disrupting cell walls, and Lefamulin, a pleuromutilin effective against drug-resistant Streptococcus pneumoniae. In addition, Zoliflodacin and Cefiderocol represent promising candidates for treating infections caused by Neisseria gonorrhoeae and Gram-negative bacteria, respectively. Despite these advancements, the development of new antibiotics is fraught with challenges, such as the complexity of clinical trials, the need for combination therapies, and the risk of rapid resistance development. Bacteriophage therapy and engineered lysins offer alternative approaches to traditional antibiotics by specifically targeting bacterial pathogens and minimizing collateral damage to beneficial microbiota. Similarly, combination therapies, which employ multiple antibiotics with distinct mechanisms, aim to enhance treatment efficacy and mitigate resistance. Examples such as trimethoprim– sulfamethoxazole and beta-lactam/beta-lactamase inhibitor combinations illustrate the effectiveness of this strategy. Immune modulation represents another innovative approach, leveraging the body’s natural defenses to combat infections. Techniques include the use of immunomodulatory compounds, such as interferon-gamma and granulocyte-colony stimulating factor, and the development of vaccines targeting drug-resistant strains. Monoclonal antibodies, such as bezlotoxumab and altastaph, target specific bacterial toxins and proteins, offering precise and effective treatment options. Nanoparticles, with their ability to disrupt microbial membranes and deliver targeted drug therapies, present a versatile and potent means of combating infections.